The Russian diaspora: a result of transit migrations or part of Russia - Irina N. Molodikova, Alla V. Kovaleva, Svetlana G. Maximova, Oksana E. Noyanzina, Daria A. Omelchenko, (Opción, 2019)
The goal of the article is to evaluate the number of the Russian diaspora and its dispersion all over the world, such as the Russian-speaking community, explore its qualitative characteristics, language behavior and attitudes to the inclusion into the Russian World through descriptive research methods. As a result, the Russian diaspora refuses to see attractive and perspective social, educational, economic, and tourist opportunities of Russia and feel positive or neutral to the Russian language and culture. As a conclusion, the Russian diaspora has a great potential of collaboration and bases policy in relation to comrades as extremely important